2016
DOI: 10.1111/1462-2920.13144
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota analysis reveals a marked shift to bifidobacteria by a starter infant formula containing a synbiotic of bovine milk‐derived oligosaccharides and Bifidobacterium animalis subsp. lactisCNCM I‐3446

Abstract: SummaryNon-digestible milk oligosaccharides were proposed as receptor decoys for pathogens and as nutrients for beneficial gut commensals like bifidobacteria. Bovine milk contains oligosaccharides, some of which are structurally identical or similar to those found in human milk. In a controlled, randomized doubleblinded clinical trial we tested the effect of feeding a formula supplemented with a mixture of bovine milkderived oligosaccharides (BMOS) generated from whey permeate, containing galacto-oligosacchari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
78
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 65 publications
(69 reference statements)
2
78
0
1
Order By: Relevance
“…We have already evaluated the effects of this prebiotic-probiotic mix in infant formula on the gut microbiota in early life, showing modulation of gut microbiota closer to that of breastfed infants (10). The aim of this study was focused on microbiota modulation effect on immune maturation: comparing the rate of infectious diarrhea and other infections.…”
mentioning
confidence: 99%
“…We have already evaluated the effects of this prebiotic-probiotic mix in infant formula on the gut microbiota in early life, showing modulation of gut microbiota closer to that of breastfed infants (10). The aim of this study was focused on microbiota modulation effect on immune maturation: comparing the rate of infectious diarrhea and other infections.…”
mentioning
confidence: 99%
“…Escherichia abundance was also higher in FF than BF infants 28 and decreased at a slower rate over time. 31 Furthermore, other results have indicated E. coli to be dominant across both groups 50 or present in similar total numbers, 51 while Penders et al 16 found this species significantly increased in FF infants at 4 wks of age. Bacteroides abundance has been shown to increase over time in BF infants; however, the timing of initial colonization is variable among infants.…”
Section: (Finland)mentioning
confidence: 92%
“…Many studies have reported that BF infants are colonized with higher proportions of microbes from the phylum Actinobacteria and less Firmicutes than FF infants. 23,25,26,28,33 Other studies report that BF infants have similar levels of Actinobacteria and Firmicutes 28,30 but lower proportions of Bacteroidetes 31,36 and Proteobacteria 26,28 compared to FF infants.…”
Section: (Finland)mentioning
confidence: 98%
See 2 more Smart Citations